Utveckling och applicering av en aviditets-ELISA för bovint respiratoriskt syncytialt virus - Lind, Agneta (2006)
Bovine Respiratory Syncytial Virus (BRSV) is a common cause of respiratory disease among young cattle. The virus causes severe losses; the herd mortality rate can sometimes be as high as 20 %. In this study the avidity (i.e the antigen binding force) of BRSV specific antibodies was measured to see if there was a difference between antibodies produced during an acute phase of infection and antibodies produced by earlier infected animals.